Merancang Kualitas Pendidikan Melalui Partisipasi Aktif Masyarakat - Akbar, Husen Ali (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2011)
One of strategy for improving the development of national education is strengthen the community aspect through active community participation to become engaged with establishing education . The role of society has been given optimally as educational development subject both locally and nationally. Because society has its own local knowledge reinforcing the future of education. However, the society itself still requires the essential elements to elaborate actively the education development through education way, one is the role of educators in intensifying education quality through active participation for all components of society. On the other hand, the education quality needs support, especially increasing awareness, knowledge and skills as social context asset in a society that relies on active participation. Therefore, we need a plan upgrading the education quality so do the quality of its people indirectly.